A compact drain current model for heterostructure HEMTs including 2DEG density solution with two subbands. (January 2016) - Deng, Wanling; Huang, Junkai; Ma, Xiaoyu; Liou, Juin J.; Yu, Fei
Highlights: An explicit and accurate scheme to compute Fermi level and surface potential. The surface potential model accounts for the two subbands in the quantum well. A single-piece drain current model for HEMTs is developed. Abstract: An explicit and precise model for two dimensional electron gas (2DEG) charge density and Fermi level ( E f ) in heterostructure high electron mobility transistors (HEMTs) is developed. This model is from a consistent solution of Schr o ¨ dinger's and Poisson's equations in the quantum well with two important energy levels. With these closed-form solutions, a unified surface potential calculation valid for all the operation regions is derived. With the help of surface potential, a single-piece drain current model is developed which is also capable of describing the current collapse effect by using a semi-empirical expression of source/drain access region resistances. Comparisons with numerical and measured data show that the proposed model gives an accurate description of E f and drain current in all regions of operation.